Early cholecystectomy may be performed in patients with Tokyo Guideline 2018 grade III acute cholecystitis who have risk factors (Annals of Medical Research, 2022)
Aim: The preferred treatment for acute cholecystitis (AC) is early cholecystectomy (EC). There are several risk factors increasing the risk of mortality for EC in Tokyo Guideline 2018 (TG18) grade III AC; and therefore, percutaneous cholecystostomy (PC) is recommended in these patients. However, the effect of these risk factors on mortality in patients having undergone EC has not been sufficiently investigated to date.Materials and Methods: In our clinic, 206 patients with AC were treated between 2015 and 2020. Thirty-one adult patients with TG18 grade III AC were included into the study. The patients were divided into two groups as EC group (n=11) and PC group (n=20). Comparisons were made between EC and PC, and the effects of risk factors on mortality were examined.Results: All patients had a score of ≥III according to American Anesthesiologists Association (ASA). The Charlson comorbidity index (CCI) was ≥4 in 72.4% of the patients, and 32.4% of patients had negative predictive factors (NPF: neurological and respiratory dysfunction, and also a total bilirubin value of ≥2 mg/dL on admission). Mortality was seen in 12 patients. Compared to patients with PC, higher definitive treatment (p˂0.001), less re-admission (p˂0.001) and less mortality (p=0.01) were seen in patients with EC. Major complications (Clavien-Dindo classification >II) and length of hospital stay were similar in both groups (p=0.60, p=0.39; respectively).Conclusion: This study showed that EC may be performed in patients with TG18 grade III AC who have risk factors. TG18 guidelines should be re-evaluated for risk factors for EC.
Keywords: Grade III acute cholecystitis; Risk factors; Cholecystectomy; Percutaneous cholecystostomy